Louise loves bake sales - Driscoll, Laura; Light, Kelly, 1970- (New York, New York : Balzer + Bray, an imprint of HarperCollinsPublishers, 2018)
"Louise loves all kinds of art. But when she has to make cupcakes for a bake sale--and everything goes wrong--can she and her brother make messy cupcakes into art?"--Back cover.
"Beginning reading, 1."
School Library Journal, December 2017
Kirkus Review, October 2017
School Library Journal
Kirkus Review
1.3
Keywords: Cupcakes -- Juvenile fiction; Art -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Siblings -- Fiction; Cupcakes -- Fiction; Art -- Fiction; Brothers and sisters -- Fiction; Readers (Publications)